The mediating effect of self-efficacy on the relationship between self-care ability and disability level in older adult patients with chronic diseases - Tiemei Wang; Senlin Wang; Senlin Wang; Nianwei Wu; Nianwei Wu; Nianwei Wu; Yan Liu (Frontiers Media S.A., 2024)
ObjectiveThis study investigates the mediating effect of self-efficacy on the relationship between self-care ability and disability level in older adult patients with chronic diseases.MethodsA convenience sampling method was used to select 372 older adult patients with chronic diseases from five tertiary hospitals in Chengdu, Sichuan Province. General demographic information was collected using a questionnaire, and self-efficacy, self-care ability, and disability were assessed using standardized scales. Data were analyzed using SPSS 26.0, and the PROCESS macro was employed to test the mediating effect of self-efficacy.ResultsThe mean score for self-efficacy was 26.09 ± 7.20, for self-care ability was 113.19 ± 23.31, and for disability was 154.19 ± 29.32. Self-efficacy was positively correlated with self-care ability (r = 0.73, p < 0.001. and negatively correlated with disability (r = −0.84, p < 0.001. and self-care ability and disability (r = −0.91, p < 0.001.. The indirect effect of self-efficacy on the relationship between self-care ability and level of disability was −0.03 (95% CI −0.08 to −0.04), accounting for 16.67% of the total effect.ConclusionSelf-efficacy partially mediates the relationship between self-care ability and disability in older adult patients with chronic conditions. Healthcare providers can improve self-care behaviours and self-efficacy in older adult patients through effective interventions to reduce the incidence of disability.